Evaluasi Kinerja Rantai Pasok Perpustakaan Institut Teknologi Telkom Purwokerto Menggunakan Supply Chain Operational Reference (SCOR) Model Berbasis Objective Matrix (OMAX) - Jihan Shinta Celina; Dwi Mustika Kusumawardani; M Yoka Fathoni (JURIKOM (Jurnal Riset Komputer), 2022)
IT Telkom Purwokerto has several facilities, one of which is the IT Telkom Purwokerto library. The library has many free facilities that can be used by visitors but must have a Student Identity Card. Facilities owned such as knowledge books for each department, computers, magazines, and others. The library itself has cooperation with several partners, both within the region and outside the region. This collaboration has several programs that have been made, but have not been implemented properly or optimally. Currently, only a few programs are still running, one of which is borrowing the collection of the program in collaboration with the Regional Library. This research on performance evaluation based on supply chain in IT Telkom Purwokerto library was conducted using the Supply Chain Operation Reference (SCOR) approach based on Objective Matrix (OMAX). SCOR divides the supply chain process into 5 processes, namely Plan (planning process), Source (procurement process), Make (production process), Deliver (delivery process), and Return (return process). The results of the analysis of the SCOR model are then calculated using the OMAX method. OMAX was chosen in conducting this research scoring system because it can determine the performance achievement of each indicator. The results of this study are recommendations for improvement for each red traffic light system, there are 13 parameters, the yellow color has 4 parameters, and the green color has 12 parameters